Вплив радіаційних дефектів на електрофізичні та детекторні властивості CdTe:Cl, опроміненого нейтронами - Kondrik, Alexandr; Kovtun, Gennadiy (PE "Politekhperiodika", Book and Journal Publishers, 2020)
A promising material for semiconductor detectors of ionizing radiation is CdTe:Cl which allows obtaining detectors with high resistivity ρ and electron mobility μn. During operation, the detector materials may be exposed to neutron irradiation, which causes radiation defects to form in crystal lattice and deep levels to appear in the band gap, acting as centers of capture and recombination of nonequilibrium charge carriers, thus reducing the detection capability. The aim of this study was to use computer simulation to investigate the mechanisms of the influence of such radiation defects on the electrophysical properties (ρ, μn) of CdTe:Cl and the charge collection efficiency η of radiation detectors based on this material.The simulations were based on the models tested for reliability. It was found that the increase of the CdTe:Cl resistivity ρ during low-energy neutrons bombardment and at the initial stages of high-energy neutrons bombardment is caused by an increase in the concentration of radiation donor defect Z (with an energy level EC – 0.47 eV), presumably interstitial tellurium, which shifts the Fermi level into the middle of the band gap. The sharp rise of ρ observed at high-energy neutron bombardment is probably caused by the restructuring of the crystalline structure of the detector material with a change in the lattice constant and with an increase of the band gap, accompanied by a change in the conductivity properties. The degradation of the detector properties of CdTe:Cl during neutron irradiation is due to the capture and recombination of nonequilibrium electrons at radiation defects: Te interstitial, Te substitutional at the cadmium site, on tellurium vacancies and cadmium vacancies. The degradation of electron mobility μn can be caused by the scattering of electrons at microscopic areas of radiation defect clusters. The increase in concentration of the defects over the volume of the crystal at their uniform distribution of up to 1016 cm–3 does not significantly affect the electron mobility at room temperature.